Analisis dan Perancangan Aplikasi E-Commerce Paradise Pet Shop Center Berbasis Web - Adli Saputra; Deddy Gusman; Safni Marwa (PT Pustaka Cendekia Group, 2025)
Petshop as of one part of business in the pet also are required to develop in application of technology.With the implementation of the technologies in of business process would be helpful petshop to improve their performance.The most business is a pet shop selling food and accessories for pets.But now there have been several business own a pet grooming shop, sterile and pet care.The method in this study is the spiral method of the System Development Life Cycle (SDLC) for system development.This method helps in website-based systems analysis and planning.For the planning of the system, Unifield Modeling Language (UML).